New Media and Chinese Society
XVII, 290 p. 22 illus., 13 illus. in color.
Keywords: This book focuses on the influence of social media on Chinese society. The respective chapters present research by top-tier communication scholars from prominent Chinese universities and offer revealing findings on the interplay between media / social media, economics and politics. To that end, both qualitative and quantitative methods based on classical theories of communication and economics are drawn upon. The book explores four main areas: the challenges and opportunities for Chinese journalism and communications, changes in Chinese economic development, influences and forecasts for Chinese politics, and the impacts on Chinese culture. As the chapter contributors hail from diverse regions within China and represent three generations of communication scholars, the book offers a comprehensive guide, helping readers understand the impact of social media on China’s development from a broad range of perspectives, and sharing insights on its impacts around the world.